Development of a Drill-and-Practice Chatbot for Enhancing English Pronunciation through Interactive Dialogue Exercises - Iskandar, Aysha Alia; Megasari, Rani; Nazir, Shah; Riza, Lala Septem (Jurnal Paedagogy, 2025)
This study aims to implement a drill and practice-based chatbot to improve English speaking skills, particularly in the aspect of pronunciation. The research employed a mixed-methods approach by combining the Research and Development (ADDIE) model with a quasi-experimental design using a pretest-posttest control group pattern. The participants consisted of 76 eighth-grade students from SMPN 5 Cirebon, divided into experimental and control groups. The instruments used included a pronunciation assessment rubric based on the Cambridge English Linguaskill Speaking Global Assessment Criteria, observation sheets, and student perception questionnaires. Data analysis was conducted through normality tests, the Wilcoxon Signed Rank Test, the Mann-Whitney U Test, and N-Gain calculation, complemented by qualitative analysis from observations and questionnaires. The findings revealed that the use of a drill and practice-based chatbot had a positive impact on improving students' pronunciation skills, although the improvement achieved remained merely in the low category, with an N-Gain score of 0.25. The chatbot was proven to provide broader, more flexible, and personalized practice opportunities for students, as well as facilitate instant feedback that is difficult to obtain in conventional learning. These results indicate that chatbots can serve as an effective supplementary medium in English language learning, particularly for practicing pronunciation both independently and in integration with classroom learning, suggesting the potential for further development and integration of chatbot technology in language education.